2015
DOI: 10.4067/s0718-95162015005000057
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes in the rhizosphere of plants growing in the vicinity of the Polish Arctowski Antarctic Station

Abstract: In maritime Antarctica soil enzymes have been little researched, mainly in the rhizosphere of the only two vascular plants that grow there: Colobanthus quitensis and Deschampsia antarctica. This study evaluated the activities of hydrolytic enzymes β-glucosidase, phosphatase and urease in the rhizospheric soils of C. quitensis and D. antarctica from three different sites in the Polish Arctowski Station in Antarctica. The sensitivity to temperature changes of the enzymes was also evaluated using two incubation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…The activities of BG, and NGA in these forest soils are within the range -or higher than reported in other studies (García et al, 2003;Trasar-Cepeda et al, 2008), and slightly higher than soils from previously investigated Antarctic ecosystems (Machuca et al, 2015). This can be an indicator of a greater C and N decomposition activity in forest ecosystems of Patagonia compared to Antarctica ecosystem, and therefore, a signal of the applicability of the enzyme activities to study C, N transformation in the soil.…”
Section: Journal Of Soil Science Andsupporting
confidence: 63%
“…The activities of BG, and NGA in these forest soils are within the range -or higher than reported in other studies (García et al, 2003;Trasar-Cepeda et al, 2008), and slightly higher than soils from previously investigated Antarctic ecosystems (Machuca et al, 2015). This can be an indicator of a greater C and N decomposition activity in forest ecosystems of Patagonia compared to Antarctica ecosystem, and therefore, a signal of the applicability of the enzyme activities to study C, N transformation in the soil.…”
Section: Journal Of Soil Science Andsupporting
confidence: 63%
“…showing the effect of temperature on urease hydrolysis (Machuca et al, 2015). In addition, a grassland soil incubated over a range of temperatures (-2 to 21°C) showed a positive relationship between urease activity and temperature, with an activation energy (E a ) of 73.4 kJ mol −1 and temperature coefficient (Q 10 ) of 2.78 (Fraser et al, 2013).…”
Section: Factors Affecting Urease Activitymentioning
confidence: 94%
“…Although urease may be constitutively synthesized in some organisms, its expression is usually under N regulation (Machuca et al, 2015). The synthesis of the enzyme is prevented when cells grow in the presence of NH 4 + as the preferred N source (Geisseler et al, 2010).…”
Section: Characteristics and Role Of Ureasementioning
confidence: 99%
“…Kumari & Rao (2017) reported that the activity of urease enzyme increased by increasing the temperature from 20 to 70°C and then decreased dramatically as the temperature increased to 90°C. Machuca et al (2015) and Al-Ansari (2000) stated that Urease activity increases with increasing temperature from 10 to 50°C. Fraser et al (2013) explained as well the significant correlation between urease activity and temperature with activation energy (Ea) of 73.4 kJmol -1 .…”
Section: Introductionmentioning
confidence: 99%